ANALISIS PEMBELAJARAN BERDIFERENSIASI DALAM MENGUATKAN KEMAMPUAN BERFIKIR KREATIF DAN LITERASI KEWARGANEGARAAN PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Puji Lestari; Sumarno; Kristina (STKIP Subang, 2024)
This research aims to describe differentiated learning in strengthening students' creative thinking and civic literacy skills. The method used was a qualitative approach, with the research sample consisting of 27 grade II students at one of the elementary schools in Semarang. The learning strategy implemented is product differentiation, where the results of the questionnaire show that creative thinking ability reaches 91.25% and civic literacy reaches 86.25%. By implementing this strategy, students are able to produce learning products that suit their interests and talents. The research results show that the product differentiation learning strategy is effective in strengthening students' creative thinking abilities and civic literacy in Pancasila Education subjects.